Natural Resource Potential on Tukad Unda River as Sustainable Tourism in Paksebali Village, Klungkung - Utama, I Wayan Wardita; Wirawibawa, Ida Bagus Gde (ASTONJADRO, 2023)
Rivers are natural resources that are important for human life. Management of rivers or watersheds (DAS) is very important for all of us, as one of them is the Tukad Unda River. Paksebali Village has a Tukad Unda Watershed (DAS) which is a tourist attraction, located about 1 kilometer east of the Kerta Gosa Klungkung tourist attraction. For local residents, Tukad Unda is certainly no stranger, the dam or dam was built on the largest river in Bali, namely the Yeh Unda river. The interesting thing about Tukad Unda is the beauty of the waterfall flow which resembles a giant curtain, stretching with the waterfall flowing evenly. This uniqueness makes Tukad Unda a tourist attraction for local people to visit. Tukad Unda has a clear river flow so that in addition to being used as a recreation area it is also for swimming and bathing by the local community. The Tukad Unda tourist attraction is also often used as a place for taking pre-wedding photos by many couples. The area on the east side of Tukad Unda, precisely on the land belonging to Paksebali Village, has built several tourist attraction facilities such as rest area facilities, restaurants, bathing places and several other facilities. The potential of the Tukad Unda river can become sustainable tourism with good arrangement and management by Paksebali Village.